Friday

April 17, 2015

April 17, 2015

Posted by **Lucia** on Tuesday, May 31, 2011 at 1:14pm.

(1 + sinØ + cosØ):(1 - sinØ + cosØ) =

(1 + sinØ) : cosØ

- Math -
**MathMate**, Tuesday, May 31, 2011 at 5:23pmWork on the left hand side:

(1 + sinØ + cosØ)/(1 - sinØ + cosØ)

multiply both the numerator and denominator by (1-sinφ+cosφ) and simplify:

((1+cosφ)^2-sin&hi;^2)/(1-sinφ+cosφ)^2

=2cosφ(1+cosφ)/[2(1-sinφ)(1+cosφ)]

=2cosφ/[2(1-sinφ)]

=cosφ/(1-sinφ)

Now multiply top and bottom by (1+sinφ)

cosφ(1+sinφ)/(1-sin²φ)

=cosφ(1+sinφ)/cos²φ

=(1+sinφ)/cosφ

**Answer this Question**

**Related Questions**

trig - how do you solve this problem? 1+sinØ/cosØ +cosØ/1+sinØ = 2secØ and cos...

Algebra 2 - As the answer to: (tanØ * cosØ/ sinØ) + cotØ * sinØ * tanØ* cscØ I ...

maths - if sinØ=cosØ then find the value of Ø

Trig - Prove the following: 1/(tanØ - secØ ) + 1/(tanØ + secØ) = -2tanØ (1 - sin...

math - Two sides of a triangle have lengths 8 m and 24 m. The angle between them...

Algebra 2 - Verify the identity , justify each step tanØ+cotØ = 1/ sin Ø cosØ

Advanced Functions/Precalculus - 1. The expression sinπ is equal to 0, ...

Topology - Find the Cartesian form of the equation, r3 = 3r cosØ.

Topology - 5. Find the Cartesian form of the equation, r3 = 3r cosØ.

maths - Find the Cartesian form of the equation, r3 = 3r cosØ